Epistemological and ethical considerations in conceptualizing and implementing human resource management - Dachler, H. Peter (Journal of business ethics, 1989)
As an example of applied social science, the field of human resource management is used to show that ethical problems are not only those of carrying out research, of professional conduct, and of the “distribution fairness” of social science knowledge. A largely overlooked ethical issue is also the implicit choices that are made as an integral part of research and implementation. First, an analysis is undertaken of the implicit assumptions, values and goals that derive from the conception of human problems in work organizations as “managing human resources”. Secondly, it is argued that such a conception is in fact a socially constructed reality with “real” consequences and not a reflection of “objective” states of human and social nature with which we have to live. Thirdly, to the extent that our implicit assumptions are in part based upon conceptual choices that are made by individuals or as a collective act of a discipline or work organization, the development of an ethical framework that could guide such choices becomes a crucial challenge for business ethics.